Pemodelan Produk Domestik Regional Bruto Sektor Pertanian dan Penyaluran Kredit menggunakan Two Stage Least Square - Prilyandari Dina Saputri; Pratnya Paramitha Oktaviana (Program Studi Statistika FMIPA UNJ, 2023)
Green economy is a concept relating to economic development which aimed to improve people's welfare by paying attention to environmental conditions. One main pillar of a green economy is economic growth which can be calculated through GDP (Gross Domestic Product). Financial institutions can play an important role in raising economic growth through optimal credit allocation. This study aims to identify the causal relationship between credit allocation from financial institutions and regional economic growth (GRDP), particularly in the green industry sector. The causal relationship that influences each other between credit allocation and Gross Regional Domestic Product (GRDP) in the agricultural, hunting, forestry, and fisheries sectors can be analyzed using the simultaneous two stage least square equation. The variables that significantly affect credit allocation are the percentage of NPL and GRDP, while the variables that significantly affect GRDP are the area of agricultural land and credit allocation. A significant causal relationship between credit distribution and GRDP shows that financial institutions can play a role in raising the growth of the green sector economy through credit allocation, especially in the green sector.